Pengaruh Jumlah Penduduk Usia Produktif, Investasi dan Tingkat Pengangguran Terbuka terhadap Pertumbuhan Ekonomi di Provinsi Jambi Periode 2005-2024 - Erisa Nevalia; Hasminidiarty Hasminidiarty (Universitas Batanghari Jambi, 2026)
Economic growth increases an economy's productive capability and national income. If the quantity of real services for production factors increases from year to year, the economy grows. And examine Jambi Province's 2005–2024 investment productive age population, open unemployment, and economic growth. To know and analyse the impact of the population of productive age, investment, and partial open unemployment on economic growth in Jambi Province in 2005–2024.